![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
1,
<=> \(\left(x-1\right)\left(x-2\right)^2=0\)
=> x=1 hoặc x=2
2,
<=>\(\left(x+1\right)\left(2x^2-3x+6\right)\)=0
=> x=-1
1.
<=> ( x -1 ) ( x - 2 ) 2 = 0
=> x = 1 hoặc x = 2
2.
<=> ( x + 1 ) ( 2x2 - 3x + 6 ) = 0
=> x = -1
![](https://rs.olm.vn/images/avt/0.png?1311)
a) (2x - 1)(x^2 - 1 + 1) = 2x^3 - 3x^2 + 2
(2x - 1).x^2 = 2x^3 - 3x^2 + 2
2x^3 - x^2 = 2x^3 - 3x^2 + 2
-x^2 = -3x^2 + 2
2x^2 = 2
x^2 = 1
=> x = 1; -1
b) (x + 2)(x + 2) - (x - 2)(x - 2) = 8x
(x + 2)^2 - (x - 2)^2 = 8x
x^2 + 4x + 4 - x^2 + 4x - 4 = 8x
8x = 8x
=> x thuộc N*
c) (x + 1)(x + 2)(x + 5) - x^3 - 8x^2 = 27
x^3 + 5x^2 + 2x^3 + 10x + x^2 + 5x + 2x + 10x - x^3 - x^2 = 27
17x + 10 = 27
17x = 27 - 10
17x = 17
=> x = 1
d) (x + 1)(x^2 + 2x + 4) - x^3 - 3x^2 + 16 = 0
x^3 + 2x^2 + 4x + x^2 + 2x + 4 - x^3 - 3x^2 + 16 = 0
6x + 20 = 0
6x = -20
x = -20/6
=> x = -10/3
![](https://rs.olm.vn/images/avt/0.png?1311)
8x2+30x+7=0
8x2+16x+14x+7=0
8x(x+2) +7(x+2)=0
(8x+7)(x+2)=0
=>\(\orbr{\begin{cases}8x+7=0\\x+2=0\end{cases}\Rightarrow\orbr{\begin{cases}x=-\frac{7}{8}\\x=-2\end{cases}}}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) (x-2)(x-1) = x(2x+1) + 2
⇔ x2 - x - 2x + 2 = 2x2 + x + 2
⇔ x2 - 2x2 - x - 2x - x = 2 - 2
⇔ -x2 - 4x = 0
⇔ x(-x - 4) = 0
⇔\(\left[{}\begin{matrix}x=0\\-x-4=0\end{matrix}\right.\)
⇔\(\left[{}\begin{matrix}x=0\\x=-4\end{matrix}\right.\)
b) (x+2)(x+2) - (x-2)(x-2) = 8x
⇔ x2 + 2x + 2x + 4 - x2 + 2x + 2x - 4 = 8x
⇔ 8x = 8x
⇒ x có vô số nghiệm
c) (2x-1)(x2-x+1) = 2x3-3x2+2
⇔ 2x3 - 2x2 + 2x - x2 + x -1 = 2x3 - 3x2 + 2
⇔ 3x = 3
⇔ x = 1
d) (x+1)(x2+2x+4) - x3 - 3x2 + 16 = 0
⇔ x3 + 2x2 + 4x + x2 + 2x + 4 -x3 - 3x2 +16= 0
⇔ 6x + 20 = 0
⇔ x = \(-\frac{20}{6}\)
.e) (x+1)(x+2)(x+5) - x3-8x2=27
⇔ (x2 +2x + x+2)(x+5) -x3-8x2=27
⇔ (x2 + 3x + 2)(x+5)-x3 - 8x2 = 27
⇔ x3 + 5x2 + 3x2 + 15x + 2x + 10 - x3 - 8x2 =27
⇔ 17x = 17
⇔ x = 1
![](https://rs.olm.vn/images/avt/0.png?1311)
\(8x^3+\left(x+8\right)^2=8\left(x+2\right)\left(x^2-2x+4\right)\)
\(8x^3+x^2+2\times x\times8+8^2=8\left(x^3+2^3\right)\)
\(8x^3+x^2+16x+64+8x^2=8\left(x^3+8\right)\)
\(8x^3+x\times\left(x+16\right)+64=8x^3+64\)
\(8x^3-8x^3+64-64+x\times\left(x+16\right)=0\)
\(x\times\left(x+16\right)=0\)
TH1:
\(x=0\)
TH2:
\(x+16=0\)
\(x=-16\)
Vậy x = 0 hoặc x = -16
![](https://rs.olm.vn/images/avt/0.png?1311)
\(8x^3+\left(x+8\right)^2=8\left(x+2\right)\left(x^2-2x+4\right)\)
\(\Leftrightarrow8x^3+x^2+16x+64=8\left(x^3+8\right)\)
\(\Leftrightarrow8x^3+x^2+16x+64=8x^3+64\)
\(\Leftrightarrow8x^3+x^2+16x+64-8x^3-64=0\)
\(\Leftrightarrow x^2+16x=0\)
\(\Leftrightarrow x\left(x+16\right)=0\)
\(\Leftrightarrow\left[\begin{array}{nghiempt}x=0\\x+16=0\end{array}\right.\)\(\Leftrightarrow\left[\begin{array}{nghiempt}x=0\\x=-16\end{array}\right.\)
\(8x^3+\left(x+8\right)^2=8\left(x+2\right)\left(x^2-2x+4\right)\)
\(\Leftrightarrow8x^3+\left(x^2+16x+61\right)=8\left(x^3+2^3\right)\)
\(\Leftrightarrow8x^3+x^2+16x+61=8x^3+61\)
\(\Leftrightarrow8x^3+x^2+16x+61-8x^3-61=0\)
\(\Leftrightarrow x^2+16x=0\)
\(\Leftrightarrow x\left(x+16\right)=0\)
\(\Leftrightarrow\left[\begin{array}{nghiempt}x=0\\x+16=0\end{array}\right.\)
\(\Leftrightarrow\left[\begin{array}{nghiempt}x=0\\x=-16\end{array}\right.\)
\(\text{Vậy x=0 hoặc x=-16 }\)
\(2x^3+x^2-8x-4\\ =\left(2x^3+x^2\right)-\left(8x+4\right)\\ =x^2\left(2x+1\right)-4\left(2x+1\right)\\ =\left(x^2-4\right)\left(2x+1\right)\\ =\left(x-2\right)\left(x+2\right)\left(2x+1\right)\)
\(2x^3+x^2-8x-4=x^2\left(2x-1\right)-4\left(2x-1\right)=\left(x-2\right)\left(x+2\right)\left(2x-1\right)\)